Details of Toll-like receptor:adapter interaction revealed by germ-line mutagenesis - Jiang, Zhengfan (National Academy of Sciences, 2006)
The immunovariant N-ethyl-N-nitrosourea-induced mutations Pococurante (Poc) and Lackadaisical were found to alter MyD88, creating striking receptor-selective effects. Poc, in particular, prevented sensing of all MyD88-dependent Toll-like receptor (TLR) ligands except diacyl lipopeptides. Furthermore, Poc-site and classical BB loop mutations caused equivalent phenotypes when engrafted into any TLR/IL-1 receptor/resistance (TIR) domain. These observations, complemented by data from docking studies and site-directed mutagenesis, revealed that BB loops and Poc sites interact homotypically across the receptor:adapter signaling interface, whereas the C-terminal α(E)-helices support adapter:adapter and receptor:receptor oligomerization. We have thus defined the TIR domain surface that mediates association between TLRs and MyD88 and the surface required for MyD88 or TLR oligomerization. Moreover, MyD88 engages individual TLRs differently, suggesting the feasibility of selective pharmacologic TIR domain receptor blockade.